Does Explicit Expectation Really Affect Preparation? - Umbach, Valentin J.; Schwager, Sabine; Frensch, Peter A.; Gaschler, Robert (Frontiers in Psychology, 2012)
Expectation enables preparation for an upcoming event and supports performance if the anticipated situation occurs, as manifested in behavioral effects (e.g., decreased RT). However, demonstrating coincidence between expectation and preparation is not sufficient for attributing a causal role to the former. The content of explicit expectation may simply reflect the present preparation state. We targeted this issue by experimentally teasing apart demands for preparation and explicit expectations. Expectations often originate from our experience: we expect that events occurring with a high frequency in the past are more likely to occur again. In addition to expectation, other task demands can feed into action preparation. In four experiments, frequency-based expectation was pitted against a selective response deadline. In a three-choice reaction time task, participants responded to stimuli that appeared with varying frequency (60, 30, 10%). Trial-by-trial stimulus expectations were either captured via verbal predictions or induced by visual cues. Predictions as well as response times quickly conformed to the variation in stimulus frequency. After two (of five) experimental blocks we forced participants by selective time pressure to respond faster to a less frequent stimulus. Therefore, participants had to prepare for one stimulus (medium frequency) while often explicitly expecting a different one (high frequency). Response times for the less frequent stimulus decreased immediately, while explicit expectations continued to indicate the (unchanged) presentation frequencies. Explicit expectations were thus not just reflecting preparation. In fact, participants responded faster when the stimulus matched the trial-wise expectations, even when task demands discouraged their use. In conclusion, we argue that explicit expectation feeds into preparatory processes instead of being a mere by-product.